Governing Islamic Marriage Registration in Indonesia: State Legibility, Administrative Burden, and Legal Recognition - Alpaten, Ulil Albab Al Aulia; Khurdianto, Risqi (Elkuator Research and Publication, 2026)
The institutionalization of Islamic marriage registration in Indonesia reflects the expanding role of the state in governing family life through legal and administrative mechanisms. Although state law requires marriages to be both religiously valid and officially registered, its implementation continues to reveal tensions among religious norms, bureaucratic procedures, and institutional practices, particularly in cases of unregistered marriages. This article examines how Islamic marriage registration is governed and how legal recognition is produced through the interaction of regulatory frameworks, administrative procedures, and judicial mechanisms. Employing a qualitative socio-legal approach, the study draws on document analysis of statutes, implementing regulations, administrative circulars, administrative instruments, and relevant decisions of the Islamic courts. The findings demonstrate that marriage registration operates as a layered governance regime in which legal recognition depends not only on religious validity but also on documentary compliance, inter-institutional coordination, administrative capacity, and access to judicial remedies. The study further shows that regulatory complexity generates multiple forms of administrative burden, including learning, compliance, and psychological costs, all of which shape citizens’ ability to obtain legally recognized marital status. Within this framework, the Islamic courts—particularly through the mechanism of isbāt nikāḥ (marriage validation)—serve as an institutional bridge between religious legitimacy and administrative recognition. The article argues that Islamic marriage registration functions as a technology of state legibility, rendering religiously based family relationships administratively visible, legally recognizable, and governable by the state. It offers a socio-legal framework for understanding how legal recognition is produced through the interaction of religious norms, administrative procedures, and institutional practices in the governance of Islamic family law in Indonesia. [Institusionalisasi pencatatan perkawinan Islam di Indonesia mencerminkan semakin luasnya peran negara dalam mengatur kehidupan keluarga melalui mekanisme hukum dan administrasi. Meskipun hukum negara mengharuskan perkawinan sah menurut agama dan dicatat oleh negara, implementasinya masih memperlihatkan berbagai ketegangan antara norma keagamaan, prosedur birokrasi, dan praktik kelembagaan, terutama dalam kasus perkawinan yang tidak tercatat. Artikel ini menganalisis bagaimana pencatatan perkawinan Islam dikelola serta bagaimana pengakuan hukum dibentuk melalui interaksi antara kerangka regulasi, prosedur administrasi, dan mekanisme peradilan. Penelitian ini menggunakan pendekatan sosio-legal kualitatif dengan analisis dokumen terhadap peraturan perundang-undangan, regulasi pelaksana, surat edaran, instrumen administrasi, dan putusan pengadilan agama yang relevan. Temuan penelitian menunjukkan bahwa pencatatan perkawinan beroperasi sebagai rezim tata kelola berlapis, di mana pengakuan hukum tidak hanya ditentukan oleh keabsahan agama, tetapi juga oleh kepatuhan dokumenter, koordinasi antar lembaga, kapasitas administratif, dan akses terhadap mekanisme yudisial. Selain itu, kompleksitas regulasi menghasilkan beban administratif yang beragam, meliputi biaya pembelajaran, biaya kepatuhan, dan beban psikologis yang memengaruhi kemampuan warga negara untuk memperoleh status perkawinan yang diakui secara hukum. Dalam konteks tersebut, Pengadilan Agama, terutama melalui mekanisme isbat nikah, berperan sebagai instrumen kelembagaan yang menjembatani kesenjangan antara legitimasi agama dan pengakuan administratif. Artikel ini berargumen bahwa pencatatan perkawinan Islam berfungsi sebagai teknologi keterbacaan negara yang menjadikan relasi keluarga berbasis agama dapat terlihat secara administratif, diakui secara hukum, dan dikelola oleh negara. Artikel ini menawarkan kerangka sosio-legal untuk menjelaskan bagaimana pengakuan hukum atas perkawinan diproduksi melalui interaksi antara norma agama, prosedur administratif, dan praktik kelembagaan dalam tata kelola hukum keluarga Islam di Indonesia.]